Nanotubes as polymer composite reinforcing additive materials – A comparative study - László Vanyorek; Emőke Sikora; Tamás Balogh; Krisztina Román; Kálmán Marossy; Péter Pekker; Tamás J. Szabó; Béla Viskolcz; Béla Fiser (Arabian Journal of Chemistry, 2020)
Nitrogen-doped bamboo-shaped carbon nanotubes (N-BCNTs) and their non-doped conventional counterparts, multiwalled carbon nanotubes (MWCNTs) were compared as polymer reinforcing additives in polyvinyl chloride (PVC) matrix. The nanotubes were synthetized by catalytic chemical vapor deposition (CCVD) method. The purity of both nanotubes was measured by thermogravimetric analysis (TGA) and found to be >91%. Further analysis on the morphology and size of the carbon nanotubes (CNTs) were performed by transmission electron microscopy (TEM). The PVC powder was impregnated with CNTs in ethanol by using tip ultrasonicator. The dispersion media was evaporated, and the CNT/PVC powder was used to produce polymer fibers. The orientation of carbon nanotubes in the PVC matrix was characterized by scanning electron microscopy (SEM), and the presence of nanotubes were confirmed in case of all PVC samples. It can be observed on the SEM images that the nanotubes are fully covered with PVC. The tensile strength of the nanotube containing samples was tested and the N-BCNT/PVC composite was found to be better in this sense, thanks to the extraordinary structure of the nanotube. In case of the N-BCNT/PVC composite the measured young modulus was 39.7% higher, while the elongation at brake decreased by 33.6% compare to the MWCNT/PVC composite. These significant differences in the mechanical properties of the composites can be explained with the stronger interaction between N-BCNTs and PVC. Keywords: N-BCNT, MWCNT, Polyvinyl chloride, Polymer composite